Politik Hukum Omnibus Law Terkait Cybercrime di Indonesia dalam Perspektif Hukum Progresif - prasetio, dicky eko (Indonesian Journal Of Law Studies, 2024)
Abstract: The problem related to the development of cybercrime in Indonesia is that there are several cybercrime developments in Indonesia that have not been regulated in statutory regulations, giving rise to a legal vacuum. Apart from that, the spread of regulations regarding cybercrime in various laws and regulations in Indonesia also has the potential to cause disharmony regarding regulations regarding cybercrime. This research aims to analyze and promote the need for legislation regarding cybercrime in a centralized and integrated manner using the omnibus law method from a progressive legal perspective. This research is normative legal research which prioritizes conceptual and statutory approaches. The research results show that the urgency of forming a centralized and integrated cybercrime law is intended to overcome various legal gaps related to cybercrime in Indonesia. Efforts to form cyber crime laws in a centralized and integrated manner using the omnibus law method viewed from a progressive legal perspective are intended to accommodate the legal needs of society because by referring to a progressive legal perspective the law exists to facilitate various human developments and needs. Apart from that, optimizing the omnibus law method in forming cyber crime laws in a centralized and integrated manner to create laws that are effective, efficient and useful for society.